Analisis Persaingan Ritel Lokal dan Nasional Secara Sosial-Ekonomi di Kota Langsa - febi febi; Chahayu Astina (IAIN Langsa, 2018)
As a newly developed city, Langsa City is one of the right areas to try. Introduced as a Service City, the city strives to meet the needs of its people. However, because Langsa City has minimal in industry, especially in medium and high scale industries, only consumptive needs can be met. Therefore, trade is a growing business, especially in retail businesses. Unfortunately, community retail businesses in recent years have experienced a decline in turnover, the main cause is the inability of local retail businesses to compete with national retail. Therefore the purpose of this study was to analyze the competition of national local economic retail business in a socio-economic way in Langsa City. Using a qualitative approach, the results show that the running of the national retail business in Langsa City has made local retailers turnover decline by an average of 30 percent and every year there are local retail businesses that have small business capital must to shut-down their businesses. The decline in the turnover of local retailers also had an effect on the reduced amount of zakah distributed, the reduction of other social contributions such as contributions to the construction of mosques, dayah, and poor people in addition to the amount of tax that also declined.Whereas in the national retail business the positive effect obtained is from tax contributions. The expectation of local retailers to the government in Langsa City is to prioritize the sustainability of local businesses in order to maintain the stability of the people’s economy.